Refreshment of Cadres and Mothers' Groups in Efforts to Improve Child Nutrition to Prevent Stunting in Kandang Mas Village - Lasmadasari, Novi; Iin Nilawati; Sutriyani; Weni Sulastri (Gayaku Publisher, 2023)
The mother's role in preventing stunting is most important, so a mother must have extensive knowledge about the nutritional value of food and how to process complementary foods for breast milk. Meanwhile, the role of health cadres plays an important role in self-care management of maternal nutrition during pregnancy as an effort to prevent stunting. One of the efforts to prevent stunting is carried out through providing nutritious food according to the needs of the child's age. The problem encountered in the Kandang Mas sub-district is that there is still a toddler's weight below the green line, which is a shared responsibility. The purpose of this community service is so that cadres can maximize their education to mothers and families in fulfilling child nutrition. The implementation of nutrition education was carried out with the participation of 2 groups of mothers of babies, toddlers and children as well as by 5 posyandu cadres. The method used is mentoring and evaluation. The result of this nutrition education education is an increase in the knowledge and skills of mothers in providing food at home so that mothers can practice it at home and increase sufficient knowledge to carry out their role as community mobilizers in preventing and treating stunting. The results of the activity are an increase in knowledge and skills of mothers in processing children's food and increased knowledge and skills of cadres in providing education and assistance to prospective mothers as well as mothers of babies/toddlers and children in their working areas. Mothers are expected to be able to apply the knowledge and skills they have acquired in this activity and convey them to other mothers around them. Cadres are expected to apply the knowledge and skills they have acquired to provide education and assistance to pregnant women in their area.